2004
DOI: 10.1023/b:phar.0000018594.26809.87
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gentamicin on serum digoxin level in patients with congestive heart failure

Abstract: The present study indicated that increase serum digoxin level when combined with gentamicin should be considered a risk factor for digitalis toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that glycopeptide antibiotics, including vancomycin and teicoplanin, as well as broad spectrum β-lactam antibiotics such as cefepime and dihydrostreptomycin can be used as adjunctive gentamicin antibiotics in the treatment process . Other studies have shown that digoxin is widely used for treatment of heart failure, while gentamicin is often used to prevent bacterial infections in heart failure patients . To evaluate specificity, we tested the drugs mentioned above (1 μM) that may be simultaneously used with gentamicin in clinical therapy (except for neomycin).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that glycopeptide antibiotics, including vancomycin and teicoplanin, as well as broad spectrum β-lactam antibiotics such as cefepime and dihydrostreptomycin can be used as adjunctive gentamicin antibiotics in the treatment process . Other studies have shown that digoxin is widely used for treatment of heart failure, while gentamicin is often used to prevent bacterial infections in heart failure patients . To evaluate specificity, we tested the drugs mentioned above (1 μM) that may be simultaneously used with gentamicin in clinical therapy (except for neomycin).…”
Section: Resultsmentioning
confidence: 99%
“…48 Other studies have shown that digoxin is widely used for treatment of heart failure, while gentamicin is often used to prevent bacterial infections in heart failure patients. 49 To evaluate specificity, we tested the drugs mentioned above (1 μM) that may be simultaneously used with gentamicin in clinical therapy (except for neomycin). The results of the specificity test demonstrate that the PaMscS1 nanopore is not disturbed by these drugs.…”
Section: Resultsmentioning
confidence: 99%
“…, 1985). Gentamycin can induce a significant increase in serum digoxin level of diabetic patients and patients with congestive heart failure (Alkadi, Nooman & Raja'a, 2004). Carvedilol also increases serum concentrations of digoxin in children (Ratnapalan, Griffiths, Costei, Benson & Koren, 2003).…”
Section: Clinical Studiesmentioning
confidence: 99%